2017
DOI: 10.1073/pnas.1711207114
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale martensitic transformation in single crystals of topological defects

Abstract: Liquid-crystal blue phases (BPs) are highly ordered at two levels. Molecules exhibit orientational order at nanometer length scales, while chirality leads to ordered arrays of double-twisted cylinders over micrometer scales. Past studies of polycrystalline BPs were challenged by the existence of grain boundaries between randomly oriented crystalline nanodomains. Here, the nucleation of BPs is controlled with precision by relying on chemically nanopatterned surfaces, leading to macroscopic single-crystal BP spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 45 publications
4
58
0
Order By: Relevance
“…In addition, by successfully fabricating BP single crystals, we have been able to analyze soft crystal nucleation and growth on chemically patterned substrates at substantial larger length scales than of atomic crystals. This allowed the observation that the BPII-BPI phase transformation assisted by a chemically patterned surface is martensitic in nature, is therefore directly analogous to classic diffusionless phase transformations found in solid crystals (13), and enriches the understanding of soft crystal crystallization and growth. To further explore BP liquid crystals as mesoscale and soft matter analogs of atomic crystals in the context of grain boundaries, in this work, a "soft heteroepitaxy" strategy, based on the accurate design and implementation of lithographically patterned chemical surfaces, is introduced to manipulate the orientation of BPs.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In addition, by successfully fabricating BP single crystals, we have been able to analyze soft crystal nucleation and growth on chemically patterned substrates at substantial larger length scales than of atomic crystals. This allowed the observation that the BPII-BPI phase transformation assisted by a chemically patterned surface is martensitic in nature, is therefore directly analogous to classic diffusionless phase transformations found in solid crystals (13), and enriches the understanding of soft crystal crystallization and growth. To further explore BP liquid crystals as mesoscale and soft matter analogs of atomic crystals in the context of grain boundaries, in this work, a "soft heteroepitaxy" strategy, based on the accurate design and implementation of lithographically patterned chemical surfaces, is introduced to manipulate the orientation of BPs.…”
Section: Introductionmentioning
confidence: 80%
“…The DTC array is interspersed by a well-defined network of liquid crystalline line defects, the lattice parameters of which are on the submicron scale for both BPI and BPII. Recent work has shown that, in the absence of grain boundaries, the crystal-crystal transition from BPI to the BPII can be extremely fast and can be understood as the liquid analog of a classic martensitic transformation (13). Because of the length scale of the lattice parameters, BPs exhibit Bragg reflections for visible light.…”
Section: Heteroepitaxy Growth Of Bp Single Crystals On Chemically Patmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when a sample cell is filled with the BPLC with a well‐treated surface, the orientation of all the lattices is in a particular direction and single color appears (Figure 1b). [ 30,36 ]…”
Section: Theorymentioning
confidence: 99%
“…On a patterned surface, interactions between the surface and the liquid crystal have different forms depending on the regions, thus forming a specific pattern. Aided by patterned confining surfaces, the BPI-BPII transformation was found to be martensitic-like, taking place in a diffusionless manner [33]. It is reasonable to expect that, specifically designed patterned confining surfaces can help discover and stabilise various complex BP structures that could be relevant to optical and photonic applications.…”
Section: Introductionmentioning
confidence: 99%